Coprecipitation of Fe/Cr Hydroxides at Organic–Water Interfaces: Functional Group Richness and (De)protonation Control Amounts and Compositions of Coprecipitates - Yandi* Hu; Jiang, Xulin; Zhang, Suona; Cai, Dawei; Zhou, Zehao; Liu, Chuan; Zuo, Xiaobing; Lee, Sang Soo (Environmental Science & Technology, 2024)
ron/chromium hydroxide coprecipitation controls the fate and transport of toxic chromium (Cr) in many natural and engineered systems. Organic coatings on soil and engineered surfaces are ubiquitous; however, mechanistic controls of these organic coatings over Fe/Cr hydroxide coprecipitation are poorly understood. Here, Fe/Cr hydroxide coprecipitation was conducted on model organic coatings of humic acid (HA), sodium alginate (SA), and bovine serum albumin (BSA). The organics bonded with SiO2 through ligand exchange with carboxyl (–COOH), and the adsorbed amounts and pKa values of –COOH controlled surface charges of coatings. The adsorbed organic films also had different complexation capacities with Fe/Cr ions and Fe/Cr hydroxide particles, resulting in significant differences in both the amount (on HA > SA(–COOH) ≫ BSA(–NH2)) and composition (Cr/Fe molar ratio: on BSA(–NH2) ≫ HA > SA(–COOH)) of heterogeneous precipitates. Negatively charged –COOH attracted more Fe ions and oligomers of hydrolyzed Fe/Cr species and subsequently promoted heterogeneous precipitation of Fe/Cr hydroxide nanoparticles. Organic coatings containing –NH2 were positively charged at acidic pH because of the high pKa value of the functional group, limiting cation adsorption and formation of coprecipitates. Meanwhile, the higher local pH near the –NH2 coatings promoted the formation of Cr(OH)3. This study advances fundamental understanding of heterogeneous Fe/Cr hydroxide coprecipitation on organics, which is essential for successful Cr remediation and removal in both natural and engineered settings, as well as the synthesis of Cr-doped iron (oxy)hydroxides for material applications.